Result of aid allocation in different sectors - JANG, Yunjeong (KDI School, 2016)
Regarding the effectiveness of aid allocation, this paper examines the aid effectiveness from the perspective of aid allocation to different sectors. The basic hypothesis of this paper is that aid allocation to economic secotrs can promote economic growth more in developing countries compared to aid allocation to other sectors. In this regard, this paper tried to prove that aid allocation to economic sectors shows the better performance in economic growth with three (3) different timing methodologies: short-term, medium-term and long-term. Also, to overcome a criticism that economic growth itself is too narrow to define the development of each country, this paper tried to broaden the concept of development into human development measured by Human Development Index (HDI). The result of this paper indicates that the disaggregated aid allocation shows the different impact on both economic growth and HDI. Aid allocation to economic infrastructure and services showed the positive and significant impact on economic growth and human welfare in the overall period, while aid allocation to social infrastructure and services showed the negative impact on economic growth in the short term and the medium term. Social aid showed even ineffectiveness on HDI in the short run and the long run. Therefore, this paper strongly proved that aid allocation to economic infrastructure and services is essential for both economic growth and human development in developing countries.
Thesis(Master) --KDI School:Master of Development Policy,2016